Aortic Stiffness, Central Blood Pressure, and Pulsatile Arterial Load Predict Future Thoracic Aortic Aneurysm Expansion - Boczar, Kevin E; Boodhwani, Munir; Beauchesne, Luc; Dennie, Carole; Chan, Kwan Leung; Wells, George A; Coutinho, Thais (Hypertension (Dallas, Tex. 1979), 2021)
Thoracic aortic aneurysm is a disease associated with high morbidity and mortality. Clinically useful strategies for medical management of thoracic aortic aneurysm are critically needed. To address this need, we sought to determine the role of aortic stiffness and pulsatile arterial load on future aneurysm expansion. One hundred five consecutive, unoperated subjects with thoracic aortic aneurysm were recruited and prospectively followed. By combining arterial tonometry with echocardiography, we estimated measures of aortic stiffness, central blood pressure, steady, and pulsatile arterial load at baseline. Aneurysm size was measured at baseline and follow-up with imaging; growth was calculated in mm/y. Stepwise multivariable linear regression assessed associations of arterial stiffness and load measures with aneurysm growth after adjusting for potential confounders. Mean±SD age, baseline aneurysm size, and follow-up time were 62.6±11.4 years, 46.24±3.84 mm, and 2.92±1.01 years, respectively. Aneurysm growth rate was 0.43±0.37 mm/y. After correcting for multiple comparisons, higher central systolic (β±SE: 0.026±0.009, P=0.007), and pulse pressures (β±SE: 0.032±0.009, P=0.0002), carotid-femoral pulse wave velocity (β±SE: 0.032±0.011, P=0.005), amplitudes of the forward (β±SE: 0.044±0.012, P=0.0003) and reflected (β±SE: 0.060±0.020, P=0.003) pressure waves, and lower total arterial compliance (β±SE: -0.086±0.032, P=0.009) were independently associated with future aneurysm growth. Measures of aortic stiffness and pulsatile hemodynamics are independently associated with future thoracic aortic aneurysm growth and provide novel insights into disease activity. Our findings highlight the role of central hemodynamic assessment to tailor novel risk assessment and therapeutic strategies to patients with thoracic aortic aneurysm.Thoracic aortic aneurysm is a disease associated with high morbidity and mortality. Clinically useful strategies for medical management of thoracic aortic aneurysm are critically needed. To address this need, we sought to determine the role of aortic stiffness and pulsatile arterial load on future aneurysm expansion. One hundred five consecutive, unoperated subjects with thoracic aortic aneurysm were recruited and prospectively followed. By combining arterial tonometry with echocardiography, we estimated measures of aortic stiffness, central blood pressure, steady, and pulsatile arterial load at baseline. Aneurysm size was measured at baseline and follow-up with imaging; growth was calculated in mm/y. Stepwise multivariable linear regression assessed associations of arterial stiffness and load measures with aneurysm growth after adjusting for potential confounders. Mean±SD age, baseline aneurysm size, and follow-up time were 62.6±11.4 years, 46.24±3.84 mm, and 2.92±1.01 years, respectively. Aneurysm growth rate was 0.43±0.37 mm/y. After correcting for multiple comparisons, higher central systolic (β±SE: 0.026±0.009, P=0.007), and pulse pressures (β±SE: 0.032±0.009, P=0.0002), carotid-femoral pulse wave velocity (β±SE: 0.032±0.011, P=0.005), amplitudes of the forward (β±SE: 0.044±0.012, P=0.0003) and reflected (β±SE: 0.060±0.020, P=0.003) pressure waves, and lower total arterial compliance (β±SE: -0.086±0.032, P=0.009) were independently associated with future aneurysm growth. Measures of aortic stiffness and pulsatile hemodynamics are independently associated with future thoracic aortic aneurysm growth and provide novel insights into disease activity. Our findings highlight the role of central hemodynamic assessment to tailor novel risk assessment and therapeutic strategies to patients with thoracic aortic aneurysm.